2002
DOI: 10.1097/00002030-200209060-00006
|View full text |Cite
|
Sign up to set email alerts
|

In patients on prolonged HAART, a significant pool of HIV infected CD4 T cells are HIV-specific

Abstract: Our findings suggest that a significant proportion of replication-competent HIV-infected CD4 T cells in these patients are memory cells directed against HIV determinants. This may provide a rationale for the therapeutic use of recombinant HIV antigens to reduce the pool of HIV-reservoir cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 30 publications
4
37
2
1
Order By: Relevance
“…The responding HIV-specific CD4 ϩ T cells sorted from these two individuals were infected at frequencies similar to those of other memory CD4 ϩ T cells, demonstrating that the HIV-specific CD4 ϩ T cells of these two subjects were not preferentially infected by HIV. In contrast, and consistent with our previous studies and those of others (11,14,17), the HIV-specific CD4 ϩ T cells from subject 19 were preferentially infected ( Table 2).…”
Section: T Cells In Hivsupporting
confidence: 92%
See 1 more Smart Citation
“…The responding HIV-specific CD4 ϩ T cells sorted from these two individuals were infected at frequencies similar to those of other memory CD4 ϩ T cells, demonstrating that the HIV-specific CD4 ϩ T cells of these two subjects were not preferentially infected by HIV. In contrast, and consistent with our previous studies and those of others (11,14,17), the HIV-specific CD4 ϩ T cells from subject 19 were preferentially infected ( Table 2).…”
Section: T Cells In Hivsupporting
confidence: 92%
“…While HIV-specific CD4 ϩ T cells are paramount in control of viral replication, these cells are preferentially infected by the virus at all stages of infection (11,14,17).…”
Section: Cd4mentioning
confidence: 99%
“…A fuller appreciation of infection within these compartments may lead to a better understanding of HIV disease pathogenesis and events that result in latent infection (13,20). For example, it has been shown that memory CD4 ϩ T cells specific for HIV are preferentially infected by the virus, which may contribute to the loss of HIV-specific CD4 ϩ T-cell responses (14,17,24). Furthermore, it has been shown that developing thymocytes at the CD4 ϩ CD8 ϩ double-positive stage can become infected by HIV and thus might contribute to infection of the peripheral naïve CD4 ϩ and CD8 ϩ T-cell pools (7,9,25,28,33,34,38,44).…”
Section: Although Human Immunodeficiency Virus Type 1 (Hiv-1) Infectimentioning
confidence: 99%
“…On the one hand, increased HIV-1 endocytosis is expected to boost the priming of anti-HIV lymphocytes, as well as the activation of anti-HIV memory lymphocytes, strengthening the anti-HIV immune response. On the other hand, this phenomenon could also favor the spread of HIV as a consequence of the increased number of activated anti-HIV CD4 1 lymphocytes, which are the preferential targets of HIV [38][39][40]. In sum, our results suggest that cell-to-cell contact-dependent HIV endocytosis by DC could be an efficient mechanism of induction of anti-HIV adaptive immunity in vivo.…”
Section: Discussionmentioning
confidence: 63%